2011
DOI: 10.3189/002214311797409820
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability of surface mass balance along a traverse route from Zhongshan station to Dome A, Antarctica

Abstract: ABSTRACT. Stakes at 2 km intervals were installed in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(55 citation statements)
references
References 29 publications
4
51
0
Order By: Relevance
“…Most recently, the SMB has been evaluated at selected sites using stake farms Urbini et al, 2008;Kameda et al, 2008;Ding et al, 2011a). In general, however, seasonal cycles are difficult to observe at sites with low accumulations (below approximately 70 kg m −2 yr −1 ), such as the polar plateau of the EAIS and windy sites, because the seasonally deposited chemical or physical signals are frequently erased or changed by the action of the nearsurface wind .…”
Section: Methodsmentioning
confidence: 99%
“…Most recently, the SMB has been evaluated at selected sites using stake farms Urbini et al, 2008;Kameda et al, 2008;Ding et al, 2011a). In general, however, seasonal cycles are difficult to observe at sites with low accumulations (below approximately 70 kg m −2 yr −1 ), such as the polar plateau of the EAIS and windy sites, because the seasonally deposited chemical or physical signals are frequently erased or changed by the action of the nearsurface wind .…”
Section: Methodsmentioning
confidence: 99%
“…No significant trend was found in accumulation rates in cores up to 100 years old before 1996 from Amundsenisen in DML . The Dome C area (Frezzotti et al, 2005;Urbini et al, 2008) has exhibited high accumulation since the 1960s, as observed along the traverse between Dome Fuji and EPICA DML, whereas no significant changes have been apparent at Dome A since 1260 (Ding et al, 2011;Hou et al, 2009). In the Talos Dome area at the border between EAP and VL, century-scale variability shows a slight increase (of a few percent) in accumulation rates over the last 200 years, in particular since the 1960s, compared with the period 1816-1965 (Frezzotti et al, 2007).…”
Section: Drivers Of Regional Precipitation 321 East Antarctic Platementioning
confidence: 99%
“…However, at two megadune field sites, 81.248 S, 124.58 E and 75.58 S, 129.58 E (Frezzotti and others, 2002b;Albert and others, 2004;Scambos and others, 2006), and over long-term snow stake fields (e.g. JARE and the Chinese Antarctic Research Expedition (CHINARE) (Motoyama and others, 2008;Ding and others, 2011)), the adjacent accumulation highs do not compensate for the near-zero glaze region extent relative to regional accumulation estimates or nearby field measurements (e.g. JARE line; Fig.…”
Section: Field Characteristics Of Wind-glaze Regionsmentioning
confidence: 99%
“…3a and b). To determine thresholds for the windglaze mapping algorithm, we use five sets of extensive, nearcontinuous field measurements of SMB: (1) the Norway-US Scientific Traverse of East Antarctica GPR profiles (Mü ller and others, 2010); (2) the JARE repeat snow stake-line measurements between 1993 and 2007 (503 stakes for 14 seasons; Motoyama and others (2008) and other references in the JARE data report series); (3) the CHINARE repeat snow stake-line measurements (528 sites, measured four times over 1997-2008Ding and others, 2011); (4) GPR profile estimates from the megadune field site near 80.248 S, 124.58 W crossing two -radiation measurements (Scambos and others, 2006;Courville and others, 2007); and (5) GPRdetermined accumulation from a set of traverses and ice cores near Talos Dome others, 2005, 2007). Locations of the field accumulation measurements are shown in Figure 3c.…”
Section: Remote-sensing Datasets and Measurement Errorsmentioning
confidence: 99%